Highly selective ppm level LPG sensors based on SnO2-ZnO nanocomposites operable at low temperature - Patil S.D.; Nikam H.A.; Sharma Y.C.; Yadav R.S.; Kumar D.; Singh A.K.; Patil D.R. (My University, 2025)
The nanoscaled SnO2, ZnO and SnO2-ZnO nanocomposite powders were prepared by microwave aided ultrasonication technique by employing centrifuge for the collection of dried powder of the materials. The fabrication of thick films of the pure ZnO and SnO2-ZnO nanocomposite powders were made by simple screen printing technique. The crystallographic phases of the pure ZnO and SnO2 doped ZnO are hexagonal in nature. The average crystallite size of 0 (pure), 1, 3, 5, 7 and 9 wt% of SnO2 doped ZnO films was found to be 30.2, 30.3, 109.7, 37.9, 36.8 and 45.6 nm, respectively. The SEM micrographs depict the porous nature of the thick films. The EDS analysis reveals that the pure ZnO and SnO2 doped ZnO films are oxygen deficient and show a semiconducting nature. The symmetric I-V characteristics depict the ohmic and non-ohmic natures of the thick films. The electrical resistivity measurements indicate a negative temperature coefficient of resistance. The gravimetric analysis shows that the average thickness of the pure ZnO thick film is 28 µm. The LPG response versus doping concentration plot suggests that the (1 wt%) SnO2 doped ZnO thick film exhibits crucial response to 100 ppm LPG at 50 °C and 100 °C. Therefore, the SnO2 doped ZnO thick film can be applicable in the field of LPG sensing with rapid response and recovery. © 2022 Elsevier B.V.